A heterotrimeric G protein-phospholipase A2 signaling cascade is involved in the regulation of peroxisomal motility in CHO cells - Huber, Christoph Michael; Saffrich, Rainer; Anton, Markus; Paßreiter, Michael; Ansorge, Wilhelm; Gorgas, Karin; Just, Wilhelm W. (Journal of cell science, 1997)
Peroxisomal motility was studied in vivo in CHO cells following transfection with a green fluorescent protein construct containing the C-terminal peroxisomal targeting signal 1 (GFP-PTS1). Time-lapse imaging and evaluation of difference images revealed that peroxisomes attach to microtubules in a Ca2+ requiring step and are transported in an ATP-dependent manner.Following microinjection of guanosine-5′-O-(3-thiotriphosphate) (GTPγS), peroxisomal movements were arrested, indicating regulation by GTP-binding proteins. The effect of GTPγS was mimicked by AlF4− and mastoparan, two drugs which are known to activate heterotrimeric G proteins. Pertussis toxin which prevents Gi/Go protein activation completely abolished the effect of GTPγS and mastoparan on peroxisomal motility suggesting that the G protein belongs to the Gi/Go class. At least one effector of the G protein is phospholipase A2 as demonstrated by the observation that the phospholipase A2 activating protein peptide efficiently blocks peroxisomal motility, and that the effect of mastoparan and AlF4− is largely abolished by various phospholipase A2 inhibitors.In summary, these data provide evidence for a new type of regulation of organelle motility mediated by a Gi/Go- phospholipase A2 signaling pathway. This type of regulation has not been observed so far with other cell organelles such as mitochondria, the endoplasmic reticulum or axonal vesicles. Thus, motility is regulated individually for each cell organelle by distinct mechanisms enabling the cell to fulfill its vital functions.
Gesehen am 22.04.2025